Marketing Strategy for Vaname Shrimp (Litopenaeus Vannamei) Case Study: Pematang Guntung Village, Teluk Mengkudu District, Serdang Bedagai Regency - Leni Handayani; M. Nazri Piransyah; Marcellina Adellini; Denny Wahyudi; Guru Maratawan; Aulia Kevin; Masita Sari; M. Dimas Ayub; Miftahul Ghania; Iyusnizar Iyusnizar; Azzahra Harahap; Akbar Sandy; Dirga Adetrya; Sudarmaji Sudarmaji; Ralando Sitompul; Hasnul Hafizd; Fachri Riza (Westscience Press, 2026)
This study demonstrates how identifying and developing marketing strategies for whiteleg shrimp farmers in Pematang Guntung Village is crucial, and the identification of appropriate marketing channels is crucial. This study is expected to formulate external and internal factors that can be used to identify strengths, weaknesses, opportunities, and threats, and recommend more effective marketing strategies, enabling farmers to increase income and obtain certainty about selling prices. The subjects of this study were six whiteleg shrimp farmers in Pematang Guntung Village, Teluk Mengkudu District, Serdang Bedagai Regency. The sampling technique used was a purposive sample with data collection using a questionnaire. This study uses a SWOT analysis which is an analysis to systematically identify various factors to formulate the right strategy in the cultivation of whiteleg shrimp (Litopenaeus vannamei). The results of the study state that the Internal factors used to see strengths are: 1). Getting assistance from the government, 2). The ordered shrimp are in accordance with consumer demand, 3). Adequate facilities and infrastructure, 4). Having a skilled, experienced and highly dedicated workforce, 5). Easy to get seeds and which are used to see weaknesses: 1). The product has not met customer demand, 2). Product promotion does not use media, 3). Unable to fulfill shrimp orders quickly, 4). The product is not durable, 5). Lack of technology that can support whiteleg shrimp cultivation. External Factors used to see Opportunities: 1). Many people interested in vannamei shrimp in the market, 2). Having a relatively high selling price, 3). Big business opportunities, 4). Technological improvements that can increase production, 5). Government policies that support and are used to see Threats: 1). A lot of competition in selling vannamei shrimp, 2). Not all of the released shrimp fry can develop well, 3). Consumer orders are not always fulfilled, 4). Lack of interest of the younger generation to cultivate vannamei shrimp, 5). Pest and disease attacks. Based on the SWOT analysis diagram that explains the external and internal factors in cell (quadrant) I shows the SO (Strength-Oppourtunities or Strengths and Opportunities) strategy, namely marketing shrimp by calculating production costs and looking at market prices. Collaborating with potential customers. Increasing the use of technology in an effort to increase production and in the SWOT matrix, namely supporting an aggressive strategy. This strategy explains that the strategy is very profitable for the business because it has opportunities and strengths in business progress, especially the vaname shrimp farming business in Pematang Guntung Village, Teluk Mengkudu District, Serdang Bedagai Regency.